Jesaja 7:14 en die maagdeIike geboorte - Pronsloo, W. S. (Verbum et ecclesia, 1997)
Isaiah 7:14 and the virgin birth. Despite the fact that Matthew 1:22-23 uses Isaiah 7:14 to legitimise the virgin birth - or, rather the virgin conception - Isaiah 7:14 can not be interpreted to be a prediction of the virgin birth. Matthew 1 :22-23 is a total reinterpretation of Isaiah 7:14 and cannot be applied as a criterion to the reading of Isaiah 7:14. These are two unique texts, each having its own junction and message.